ACCEPTING MOODLE BY ACADEMIC STAFF AT THE UNIVERSITY OF JORDAN: APPLYING AND EXTENDING TAM IN TECHNICAL SUPPORT FACTORS - AlQudah, Ayman Ahmed (European Scientific Journal, ESJ, 2014)
The Technology Acceptance Model’s (TAM) extension is applied to identify staff attitudes towards Moodle. Quantitative and qualitative approach to collect the required data done by distributing questionnaires and conducting semi-structural interviews. The results indicate that the perceived ease of use (PEOU) is a more significant barrier in adopting Moodle. This means the instructors tend to use Moodle if they think Moodle is easy to use. (PEOU) refers to the degree to which instructors believe Moodle usage would be free of effort and it would easy to handle. Only 18.8 % of instructors find uploading materials for students using Moodle is easy in opposed to 27.5% of instructors who believe that Moodle is not easy to upload materials. Apparently, 27.5% tend to be neutral and can’t decide if Moodle is easy for uploading materials or not.